Improve the skill of dropping techniques with catches in pencak silat through the section method - Wardoyo, Hendro; Widiastuti, Widiastuti; Novian Saputro, Eko (Universitas Nusantara PGRI Kediri, 2025)
The background of this research is the need to increase the effectiveness of the dropping technique with a catch in pencak silat athletes because mastery of this skill is very important to improve performance in the fighter category. This study aims to improve the drooping technique with catches at PPS Merpati Putih Bekasi. The subjects of this study are beginner pencak silat athlete Merpati Putih in Bekasi, fighter category. The youth category consists of male athletes and female athletes. The method used in this study is the section method with Action Research. The indicators measured in this study are preparatory movement, execution movement, follow-up movement, and final movement. Based on the study's results, conclusions can be obtained. Action Research and the section method in training can improve the dropping technique with catches at pencak silat Merpati Putih Bekasi. With one cycle of action research. The success rate of athletes in the pre-test amounted to 4 or 18.18%, then after being trained with the part-by-part method in the first cycle, the success of athletes reached 20 people or 90.91%. From the research data, a tcount of 21.3 was obtained with a significant level of 0.05, and ttable was 1.72, then tcount (21.3) > ttable (1.72) means that there was a significant increase between the pre-test and the post-test.